PERANCANGAN DAN IMPLEMENTASI SISTEM MANAJEMEN MUTU ISO 9001:2015 DIDUKUNG DENGAN PENERAPAN 5S DI CV. XYZ, MADIUN - Noveryan Dwi Puraga; Yenny Sari; Rahman Dwi Wahyudi (Perpustakaan Universitas Surabaya, 2018)
CV. XYZ was a furniture company in Madiun City, East Java, that operated since 1996. This company used the concept of engineering to order, which meant designing the product came first before producing the item according to the accepted order. The analysis of gap in compliance to the QMS ISO 9001:2015 requirements showed that there were 16% compliance to the ISO requirement, 31% of half-compliance, and 53% of non-compliance. The result of early 5S audit revealed that the level of compliance in three areas were: owner area (41%), administration area (30%), production area (25%). The drafting of QMS ISO 9001:2015 was done through risk and opportunity analysis (risk register) by giving action plan to each occurring risks and creating quality objectives for the company. This research resulted in documented information in the form of one quality manual, sixteen quality procedures, four work instructions, and fifteen quality forms. The result of 5S implementation was done in production area, by cleaning the production floor, sorting and discarding waste, etc. Action plan were implemented to prevent the highest risk in strategic level and operational level. By far, ten action plans were implemented, three action plans were half-implemented, and one action plan was not implemented yet. In five quality objectives being monitored, two had been achieved and the other three had not been achieved yet.